Nonlinear Analysis of Shaking Conveyers with Single-mass; Crank-and-Rod Exciters - Alisverisci, G. Fusun (AMER INST PHYSICS, 2011)
The single mass, crank-and-rod exciters shaking (vibrational) conveyers has a trough supported on elastic stands which are rigidly fastened to the trough and a supporting frame. The trough is oscillated by a common crank drive. This vibration causes the load to move forward and upward. The moving loads jump periodically and move forward with relatively small vibration. The movement is strictly related to vibrational parameters. This is applicable in laboratory conditions in the industry that accommodate a few grams of loads, up to those that accommodate tons of loading capacity. In this study is the transitional behavior across resonance, during the starting of a single degree of freedom vibratory system excited by crank-and-rod. A loaded vibratory conveyor is more safe to start than an empty one. Shaking conveyers with cubic nonlinear spring and ideal vibration exciter have been analyzed analytically for primary resonance by the Method of Multiple Scales, and numerically. The approximate analytical results obtained in this study have been compared with the numerical results, and have been found to be well matched.
Keywords: Shaking conveyers; crank-and-rod exciters; stability; nonlinear analysis; TRANSITION; RESONANCE; Physics